15 Oral apixaban compared to subcutaneous enoxaparin for thromboprophylaxis in women undergoing surgery for suspected gynecologic cancer: final results of a multi-institutional randomized, controlled trial. (18th September 2019) - Guntupalli, S; Brennecke, A; Babayan lisa, LM; Sheeder, J; Cheng, G; Breed, C; Ramzan, A; Wheeler, L; Behbakht, K; Corr, B; Lefkowits, C; Matsuo, K; et al.
Abstract : Objectives: Venous thromboembolism (VTE) is a serious complication following gynecologic oncology surgery with 26% DVT and 9% pulmonary embolism rates. Current guidelines recommend subcutaneous enoxaparin for thromboprophylaxis. We evaluated safety of apixaban (oral factor Xa inhibitor) versus enoxaparin for post-operative thromboprophylaxis in women with suspected gynecologic cancer. Methods: A randomized study determined safety (major bleeding) of apixaban versus enoxaparin. Secondary outcomes included VTE, adverse events (AE), satisfaction. Women (18–89) were randomized to 28-days of 2.5mg apixaban BID or 40mg enoxaparin QD and followed for 90-days. Chi square and Fisher's exact statistics were used; P< 0.05 determined significance. Results: Four hundred women completed therapy (mean age 56.6 years; mean BMI 28.5). Groups were similar for race, cancer diagnosis/stage, and surgery. Seventy-eight percent of surgeries were open laparotomies; 70% involved hysterectomy. Two major bleeding events occurred on treatment: 1/205 in apixaban arm vs.1/195 in enoxaparin arm (OR=0.95; 95%CI: 0.06–15.1; P =0.972). Five VTE events occurred: 2/205 vs. 3/195 respectively (OR=0.63; 95%CI: 0.12–3.75; P =0.616). Women receiving apixaban were 98% less likely to report pain (OR= 0.02, 95% CI 0.01–0.05, P< 0.001) and 99% less likely to report difficulty administering treatment (OR= 0.01, 95% CI 0.001–0.13, P< 0.001) compared to enoxaparin. There were 97 related AEs; AEs were rare (2%) and similar: wound infection ( P =0.745), wound dehiscence ( P =0.100), arthralgia ( P =0.321), dizziness ( P =0.078), vaginal bleeding ( P =0.410), and headache ( P =0.875). Conclusions: Apixaban is a safe alternative to enoxaparin for thromboprophylaxis following gynecologic oncology surgery. Women taking apixaban had less pain and difficulty administering treatment. Efficacy of apixaban to prevent VTE is hypothesized as equivalent to enoxaparin.